Anti-inflammatory effect of Adelia ricinella L. aerial parts. (16th January 2021) - Berenguer-Rivas, Clara Azalea; Escalona-Arranz, Julio César; Llauradó-Maury, Gabriel; Van der Auwera, Anastasia; Piazza, Stefano; Méndez-Rodríguez, Daniel; Foubert, Kenn; Cos, Paul; Pieters, Luc
Abstract: Objective: To investigate the main chemical components and the anti-inflammatory activity of extracts of Adelia ricinella L. aerial parts. Methods: Three extracts obtained by soxhlet extraction and ethanol/water mixtures were evaluated in their chemical composition by UPLC-DAD-MS/MS. The in vitro anti-inflammatory activity of the prepared extracts was assessed through three different assays: COX-1 and COX-2 enzymatic inhibition, cell-based COX assays on RAW264.7 macrophages (ATCC) measuring the COX-2 protein expression by Western blot and the measurement of the PGE2 concentration in the supernatants of the culture medium. Also was determinate the effect of the three extracts on the RAW 264.7 cell viability. Key findings: Few differences in the phytochemical profile were found between the three prepared extracts, identifying a blend of thirteen flavonoids derived from luteolin and apigenin, with orientin as main constituent. Plant extracts (alcoholic and aqueous) did not affect the macrophage cell viability (IC50 > 256 μg/ml) and significantly reduced COX-1 and COX-2 enzyme activities. Additionally, COX-2 expression and PGE2 release were suppressed after 24 h of LPS stimulation and treatment with plant extracts (8–64 µg/ml). Conclusions: A. ricinella extracts showed the ability to reduce the inflammatory effect exerted by LPS in murine macrophages. However, further studies should confirm their anti-inflammatory activity.